Information Security Applications 8th International Workshop, WISA 2007, Jeju Island, Korea, August 27-29, 2007, Revised Selected Papers - Sehun, Kim; Yung, Moti; Lee, Hyung-Woo (Security and Cryptology ;, 2007)
The 8th International Workshop on Information Security Applications (WISA 2007) was held on Jeju Island, Korea during August 27-29, 2007. The workshop was sponsored by the Korea Institute of Information Security and Cryptology (KIISC), the Electronics and Telecommunications Research Institute (ETRI) and the Ministry of Information and Communication (MIC). WISAaimsatprovidingaforumforprofessionalsfromacademiaandindustry to present their work and to exchange ideas. The workshop covers all technical aspects of security applications, including cryptographic and non-cryptographic techniques. We were very pleased and honored to serve as the Program Committee Co-chairs of WISA 2007. The Program Committee received 95 papers from 20 countries, and accepted 27 papers for the full presentation track. The papers were selected after an extensive and careful refereeing process in which each paper was reviewed by at least three members of the Program Committee. In addition to the contributed papers, the workshop had three special talks. Moti Yung gave a tutorial talk, entitled "Somebody You Know: The Fourth Factor of Authentication." Kihong Park and Nasir Memon gave invited talks, entitled "Reactive Zero-Day Attack Protection" and "Securing Biometric T- plates," respectively. Many people deserve our gratitude for their generous contributions to the success of the workshop. We would like to thank all the people involved in the technical program and in organizing the workshop. We are very grateful to the ProgramCommitteemembersandtheexternalrefereesfortheir timeande?orts in reviewing the submissions and selecting the accepted papers. We also express our special thanks to the Organizing Committee members for their hard work in organizing the workshop.